2021
DOI: 10.3389/fsufs.2021.659047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Topping and Spacing on Growth, Yield, and Fruit Quality of Tomato (Solanum lycopersicum L.) Under Greenhouse Condition

Abstract: Tomato is an important vegetable in Ghanaian diet and contributes enormously in livelihood improvement. Tomato production is threatened by a high prevalence of biotic and abiotic stresses as well as increased postharvest losses and poor agronomic practices, thereby resulting in massive importation of tomato and its products to meet the local demands. The recent introduction of greenhouse vegetable cultivation technology in Ghana is a sustainable attempt in addressing and ensuring year-round production of veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…There have been reports of great increases in tomato yield and yield components when recommended plant spacing was used [33][34][35]. A recent study by Nkansah et al [36] suggested plant spacing of 0.2 × 1.3 m for greenhouse tomato production.…”
Section: Plant Spacing and Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…There have been reports of great increases in tomato yield and yield components when recommended plant spacing was used [33][34][35]. A recent study by Nkansah et al [36] suggested plant spacing of 0.2 × 1.3 m for greenhouse tomato production.…”
Section: Plant Spacing and Densitymentioning
confidence: 99%
“…Topping has been shown to improve fruit quality and yield by causing assimilates to be redistributed to developing fruits [44,45]. In the Solanaceae family, topping improved yield and yield components in eggplant [46], pepper [47] and tomato [36]. According to Nkansah et al [36], tomato yields were increased by topping at truss 2.…”
Section: Pruning Topping and Training/trellisingmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato (Solanum lycopersicum Mill) production, as a popular cash crop business occupies an important position due to its versatile usability throughout the world [19][20][21]. Tomatoes are a high-yielding, high-valued and high water requirement crop, cultivated in both open and protected facilities [22,23].…”
Section: International Journal Of Environmental Sciences and Natural ...mentioning
confidence: 99%
“…Studies have examined the adoption of improved production practices (Asante et al, 2013;Huat et al, 2013;Masood et al, 2018;Frimpong et al, 2021;Gotame et al, 2021;Nkansah et al, 2021;Shrestha et al, 2021;Iqbal et al, 2022;Akomdo et al, 2023). Most of these studies focused on the agronomic effects (Masood et al, 2018;Gotame et al, 2021;Shrestha et al, 2021;Iqbal et al, 2022), while others investigated such adoption decisions under different production settings.…”
Section: Introductionmentioning
confidence: 99%